Gamification on Working Memory: The Use of Puzzles in Advancing Education Outcomes in Qatari Public Schools - Makki , Fadi; Sedas, Paola Schietekat; Klauznicer, Helena Vlahinja (Issues in Social Science, 2024)
This paper investigates the effect of gamification tools on the learning outcomes of an educational program that uses football to convey keywords representing the life skills students are expected to develop throughout the program. During each session, three keywords were reinforced. To enhance the retrieval abilities of students (n=732) from Grades 3 to 6, a behavioural intervention was rolled out, consisting of six sets of puzzles that each formed a keyword. Students in the treatment group were asked to assemble the puzzles corresponding to the three keywords of the session, while control students followed the standard planned reflection. Students were then quizzed on their ability to recognize the keywords from among a list of words. The intervention resulted in a 14.2% increase in the number of correct words identified, significant at the 5% level, with the keyword ‘communication’ showing a retention rate 25.3 percentage points higher in the treatment group compared to control. Such findings support the implementation of gamification tools in educational settings, as they can be helpful in developing students’ working memory, which is instrumental in bridging abstract concepts and practical, applicable life skills.